Low-complexity channel estimation in massive MIMO based on Kaptyn series expansion - Bing WANG; Zhengquan LI; Feng YAN; Lianfeng SHEN (Dianxin kexue)
In order to reduce the complexity of the massive MIMO channel estimation, a channel estimation method based on Kapteyn series expansion was proposed. By using Taylor series to expand the inversion, the complexity was greatly reduced. In order to improve the Taylor-MMSE estimation of the convergence rate, Kapteyn series was used to expand covariance matrix. The simulation result shows that the mean square error of Kapteyn-MMSE estimation converges faster than Taylor-MSME. It is insufficient that the complexity of Kapteyn-MMSE slightly higher than the complexity of Taylor-MMSE, but still far less than the complexity of classical MMSE algorithm.